2020
DOI: 10.1080/17452759.2020.1795209
|View full text |Cite
|
Sign up to set email alerts
|

3D/4D-printed bending-type soft pneumatic actuators: fabrication, modelling, and control

Abstract: This article reviews soft pneumatic actuators (SPAs) that are manufactured entirely via additive manufacturing methods. These actuators are known as four-dimensional (4D)-printed SPAs and can generate bending motions in response to either pressurized or vacuum (negative pressure) air stimulus after fabrication. They are characterized by geometrical and material factors that determine their motion trajectory, and the force they exert on manipulated soft objects in delicate applications such as food handling and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
59
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 121 publications
(60 citation statements)
references
References 170 publications
(213 reference statements)
0
59
0
1
Order By: Relevance
“…Besides that, based on the simulation result, non-uniformed hollow spaces pattern displayed favourable result that could be a reference for future research in order to design the suitable pattern for the 4D PLA model. The possible advanced applications of 4D printing are medical devices for stents placed into blood vessels, drug capsules that release medicine, home appliances for control and that adjust according to humidity and heat, footwear and clothes, implants for humans and animals made from biocompatible materials, soft robots that can be activated without reliance on an electric device, smart valves and sensors for infrastructure lines [178][179][180][181][182][183]. Adapted from Alief et al [177] with copyright permission of AIP Conference Proceedings.…”
Section: D and 4d Printings Of Pla Biocompositementioning
confidence: 99%
“…Besides that, based on the simulation result, non-uniformed hollow spaces pattern displayed favourable result that could be a reference for future research in order to design the suitable pattern for the 4D PLA model. The possible advanced applications of 4D printing are medical devices for stents placed into blood vessels, drug capsules that release medicine, home appliances for control and that adjust according to humidity and heat, footwear and clothes, implants for humans and animals made from biocompatible materials, soft robots that can be activated without reliance on an electric device, smart valves and sensors for infrastructure lines [178][179][180][181][182][183]. Adapted from Alief et al [177] with copyright permission of AIP Conference Proceedings.…”
Section: D and 4d Printings Of Pla Biocompositementioning
confidence: 99%
“…Multi jet fusion (MJF), a newly developed powder bed fusion technology, significantly accelerates the printing speed because it utilises a 'face (slice)body' accumulation process (O'Connor, Dickson, and Dowling 2018;Goh, Sing, and Yeong 2020;Yap, Sing, and Yeong 2020;Zolfagharian et al 2020). In the MJF printing process, fusing and detailing agents (for absorbing IR radiation and tailoring dimensional accuracy, respectively), and infrared lamps are used to heat and fuse polymer powders into predefined 3D geometries (Habib et al 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Polymer laser sintering (PLS) is a type of additive manufacturing technology that uses either a continuous or pulse mode laser beam to fuse powder particles to form 3dimensional parts from computer-aided data [1]. Polymer laser sintering is broadly referred to as selective laser sintering (SLS), which is described as a technology that uses a power source to sinter and bind powdered materials, such as polyamide or polypropylene [2]. The PLS technique has become widely popular for the processing of polymers because of its ability to achieve good geometrical accuracy, good surface finish, and excellent mechanical properties of the manufactured parts.…”
Section: Introductionmentioning
confidence: 99%
“…The laser power, scanning speed, hatch distance, and layer thickness are the most easily adjustable process parameters in PLS. The four parameters determine the amount of laser energy that is transferred to the powder and are related to one another as shown by Equations (1) and (2) [5]. Previous studies have shown that increasing laser energy density increases part density and mechanical properties, but in turn Table 1: A summary of the suitable process parameters for various commercially available polypropylene powders based on best mechanical properties [8].…”
Section: Introductionmentioning
confidence: 99%